Basic economics - Mastrianna, Frank V. (Australia : South-Western/Cengage Learning, 2013)
This book delivers a streamlined, straightforward introduction to the fundamentals of macro- and microeconomics, while addressing some of the most stimulating issues affecting the world today. You will engage students with timely discussions of monetary policies and the labor market, as well as the recent financial market collapse and housing crises. This very successful text also presents in a concise, 19-chapter format, which can be covered in single quarter or semester, and includes a wealth of student applications and instructor supplements to assist with course planning and teaching.
Previous ed.: 2010.
Includes bibliographical references and index.
Buku bacaan asas fakulti
Keywords: Economics; Economics -- Textbooks; Economics -- Study and teaching (Higher).